Can paracetamol (acetaminophen) be administered to patients with liver impairment? - Hayward, Kelly L. (Br J Clin Pharmacol, 2015)
Although 60 years have passed since it became widely available on the therapeutic market, paracetamol dosage in patients with liver disease remains a controversial subject. Fulminant hepatic failure has been a well documented consequence of paracetamol overdose since its introduction, while short and long term use have both been associated with elevation of liver transaminases, a surrogate marker for acute liver injury. From these reports it has been assumed that paracetamol use should be restricted or the dosage reduced in patients with chronic liver disease. We review the factors that have been purported to increase risk of hepatocellular injury from paracetamol and the pharmacokinetic alterations in different pathologies of chronic liver disease which may affect this risk. We postulate that inadvertent under‐dosing may result in concentrations too low to enable efficacy. Specific research to improve the evidence base for prescribing paracetamol in patients with different aetiologies of chronic liver disease is needed.